The Effectiveness of Mediation in Divorce Case Resolution - Muhammad Rayyan Aulia; Teuku Muttaqin Mansur; Nurdin MH (International Journal of Law and Society, 2026)
This study examines the effectiveness of mediation in resolving divorce cases at the Banda Aceh Sharia Court and the Jantho Sharia Court based on Supreme Court Regulation No. 1 of 2016. This study aims to analyze the implementation of mediation, identify factors influencing its effectiveness, and determine efforts to improve the effectiveness of mediation in divorce cases. The method used is a legal-empirical approach with a qualitative methodology through interviews and literature review. The research results indicate that the implementation of mediation has been in accordance with the provisions of Supreme Court Regulation No. 1 of 2016; however, its success rate remains low, rendering it ineffective. Factors influencing the effectiveness of mediation include the mediator’s competence, the parties’ strong desire to divorce, prolonged domestic conflicts, and the influence of religious figures within the community. Efforts to improve the effectiveness of mediation are carried out by enhancing the competence of mediators, educating the parties on the benefits of mediation, and optimizing the mediation process within the Sharia Court.